2019
DOI: 10.1021/acs.joc.9b01964
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Hydrogenation of Activated Aryl Imines Catalyzed by an Iron(II) P-NH-P′ Complex

Abstract: Reports of the use of first row transition metal complexes for the catalytic AH of imine are limited. In 2011 Beller and coworkers reported that a range of N-aryl substituted imines were hydrogenated to amines with ee ranging from 88 to 98% using Knölker's iron complex FeH(CO)2(Cp'OH) (5 mol%) in combination with the homochiral phosphoric acid (S)-TRIP (1 mol%) at 50 bar H2 and 65 °C. 23 In 2014 our group reported that an iron complex [FeBr(CO)2(L 1)]BF4 with the asymmetric ligand (S,S)-PPh2CHPhCHMeNHCH2CH2P i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 49 publications
1
13
0
1
Order By: Relevance
“…According to calculations, the hydride transfer and the splitting of dihydrogen had similar energy barriers and could define the rate limiting step and the turn-over frequency depending on the ketone substrate. Finally, the calculated energies of the assumed pro-S and pro-R transition states were consistent with the observed enantioselectivity Mechanism of the AH of ketones catalysed by iron(II) complex 40a based on a chiral PNHP ligand by Morris et al In a recent contribution, Morris et al reported the application of an unsymmetrical iron PNHP′ pre-catalyst (41a) for the AH of imines activated with N-diphenylphosphinoyl (Scheme 46)[125]. At the exception of dialkyl derivatives (35% ee), yields (up to 85%) and enantioselectivities (up to 99% ee) were high.…”
supporting
confidence: 70%
“…According to calculations, the hydride transfer and the splitting of dihydrogen had similar energy barriers and could define the rate limiting step and the turn-over frequency depending on the ketone substrate. Finally, the calculated energies of the assumed pro-S and pro-R transition states were consistent with the observed enantioselectivity Mechanism of the AH of ketones catalysed by iron(II) complex 40a based on a chiral PNHP ligand by Morris et al In a recent contribution, Morris et al reported the application of an unsymmetrical iron PNHP′ pre-catalyst (41a) for the AH of imines activated with N-diphenylphosphinoyl (Scheme 46)[125]. At the exception of dialkyl derivatives (35% ee), yields (up to 85%) and enantioselectivities (up to 99% ee) were high.…”
supporting
confidence: 70%
“…1b) [28][29][30] . In view of current interest in the development of earthabundant metal catalysts in asymmetric hydrogenation [31][32][33][34][35][36][37][38][39][40][41] , which are inexpensive and environmentally friendly, the use of nickel has drawn increasing attention 24,[31][32][33][34][35][36][37][38][39][40][41] . Although Nicatalyzed asymmetric reduction has seen rapid development, the asymmetric hydrogenation of imines is still in its infancy 24,[42][43][44] .…”
mentioning
confidence: 99%
“…To develop an alternative synthetic route to obtain these imidoyl sulfoxonium ylides, we explored a strategy for imine group formation from β-keto sulfoxonium ylides ( 3 ) and anilines ( 4 ) (method B, Scheme ). To perform this transformation, TiCl 4 was applied as a Lewis acid, since this titanium complex is already known to efficiently promote the formation of imines . The reaction between dimethyloxosulfonium benzoylmethylide ( 3a ) and aniline ( 4a ) provided compound 2a in 83% yield after 40 h at room temperature in CH 2 Cl 2 as the solvent.…”
Section: Resultsmentioning
confidence: 99%